Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1116/1.2968696
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Cl2, Cl2∕O2, and Cl2∕N2 inductively coupled plasma processes for etching of high-aspect-ratio photonic-crystal holes in InP

Abstract: An extensive investigation has been performed on inductively coupled plasma etching of InP. An important motivation for this work is the fabrication of high-aspect-ratio holes for photonic crystals. The essential chemistry is based on Cl 2 with the addition of N 2 or O 2 for sidewall passivation. The influence of different process parameters such as gas flows, temperature, pressure, ion energy, and inductively coupled plasma power on the hole geometry is presented. It is concluded that photonic crystals can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…In our InP etching model, atomic nitrogen N is introduced as a neutral species yielding to the passivation reactions along the etched surface. Indeed, previous experimental works have shown the passivating role of N 2 used in InP etching under chlorine‐based plasma 3, 4, 17, 19, 35. Lee et al4 showed that for %N 2 lesser than 30%, the isotropic etching was observed in PhC hole while for 60%N 2 , the anisotropy of PhC patterns was improved but with rough sidewalls on the bottom of holes.…”
Section: Inp Etching Simulatormentioning
confidence: 99%
See 2 more Smart Citations
“…In our InP etching model, atomic nitrogen N is introduced as a neutral species yielding to the passivation reactions along the etched surface. Indeed, previous experimental works have shown the passivating role of N 2 used in InP etching under chlorine‐based plasma 3, 4, 17, 19, 35. Lee et al4 showed that for %N 2 lesser than 30%, the isotropic etching was observed in PhC hole while for 60%N 2 , the anisotropy of PhC patterns was improved but with rough sidewalls on the bottom of holes.…”
Section: Inp Etching Simulatormentioning
confidence: 99%
“…This was attributed to the formation of passivating layer which protected the vertical sidewalls of the features from the reactive chlorine species. Carlstrom et al17 have reported the experimental results concerning the etched InP PhC for 200 nm hole under chlorine ICP plasma. For pure Cl 2 , bowing defect characterized by the local lateral etching was observed for p = 1.4 mTorr, substrate surface temperature T s = 200 °C and $Q({\rm Cl}_{2} ) = 14\;{\rm sccm}$ .…”
Section: Inp Etching Simulatormentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,23 All these works pointed out that pure Cl 2 plasma caused severe undercuts and that an additive gas such as N 2 or O 2 should be introduced to achieve anisotropic etching of high aspect ratio features. 15,17,23 All these works pointed out that pure Cl 2 plasma caused severe undercuts and that an additive gas such as N 2 or O 2 should be introduced to achieve anisotropic etching of high aspect ratio features.…”
Section: Single Step Etchingmentioning
confidence: 99%
“…Hence, a combination of a technologically wellestablished tunnel-junction [3] with a photonic-crystal (PhC) structure [4][5][6] might be the best solution for phosphide based VCSELs. Although the PhC technology is still developing, the aspect ratios (hole depth to hole diameter ratio) of about 15-20 [7][8][9] achievable nowadays are encouraging for such PhC VCSEL design. This motivates the study of the impact of the hole depth on the modal behaviour of PhC VCSELs to define the smallest aspect ratio assuring good performance.…”
mentioning
confidence: 99%